The partisan [videorecording (DVD)] - Marquand, James; Polanski, Morgan; McDowell, Malcolm; Ingvar Sigurðsson, 1963- (Brainstorm Media, 2025)
A Polish spy who works for the British during the Second World War. After a betrayal, she is compromised in Warsaw and finds herself in a murky world of treachery.